Syaria’s Maqashid Implementations in Resources Related to the Green Economy - Kurniasih, Dwi (EJESH: Journal of Islamic Economics and Social, 2025)
Responsible and efficient use of natural resources is vital to the long-term sustainability of our planet. Sustainable Resource Management involves balancing the needs of economic development, social welfare, and environmental protection. Where in practice the management of natural resources is the practice of the concept of the fulfilment of basic human needs framed in the “Maqahid Sharia’ah”. For this research using the method of research used is by using the qualitative approach of library research, and method of collection of data literature review forms of journals and related documents. Studies have shown that the concept of the so-called "green economy" is included in the implementation of the maqashid shariah because it prioritizes the elements of maslahah and adl to the well-being of the community, such as reducing inequalities of poverty. environmental balance, and as a tool for creating new jobs. Moreover, the concept of a green economy, which means managing natural resources without damaging nature, is reflected in Islamic environmental ethics. The success of a green economy depends on firm government policies and implementation, as well as public awareness.